Community Empowering Dalam Meningkatkan Kepatuhan Perawatan Diabetes Mellitus pada Kelompok Lanjut Usia Di Masyarakat - Wirda Hayati; Marianthi, Dewi; Halimatussakdiah; Ritawati (Bansigom Na Publisher, 2024)
Diabetes mellitus is a prevalent chronic condition among the elderly and can lead to severe complications if not managed properly. Adherence to diabetes care is crucial for reducing the risk of complications and improving quality of life. This article explores community empowerment strategies for enhancing adherence to diabetes care among elderly individuals within the community. The focus is on examining effective community empowerment methods that support diabetes management, including health education, social support, and community-based outreach. The article reviews various interventions implemented in communities to increase knowledge, skills, and motivation among the elderly for adhering to their diabetes care plans. Research findings indicate that community empowerment involving health education, support groups, and family involvement can significantly improve adherence to diabetes care. These insights are expected to contribute to the development of more effective public health programs for managing diabetes in the elderly population.